The Spanish monarchy and the creation of the Viceroyalty of New Granada (1717-1739) - Eissa-Barroso, Francisco A. (Brill, 2015)
The viceregal institution in the Spanish world under the Habsburgs – Northern South America at the turn of the eighteenth century – Reform under the first Bourbon: the dawn of the administrative monarchy – Giulio Alberoni, reform through the via reservada and the first creation of the Viceroyalty of New Granada – Two architects and faulty foundations' explaining the suppression of the First Viceroyalty of New Granada – The viceroy's subjects: New Granada under the First Viceroyalty – The end of reform: Jose Patino and New Granada's government between 1724 and 1739 – The Council of Indies and the War of Jenkins' Ear: the second creation of the Viceroyalty of New Granada.
10.1163/9789004308794
Keywords: Spanien; Neugranada; Gründung